Combination antifungal therapy for invasive fungal infections in children and adults. Issue 5 (May 2013) - Hatipoglu, Nevin; Hatipoglu, Husem
Although therapeutic first-line approaches have been established in severely immunosuppressed patients with a high risk of invasive fungal infections, treatment modalities for cases with unsatisfactory outcome have not been well defined, especially for the pediatric age gap. Therapy with coadministration of two or three antifungals has been applied by clinicians in difficult-to-treat infections, which still have no support from randomized, controlled clinical trials. The most prevailing reason for a combination regimen is to broaden the antimycotic spectrum, which may even result in antagonistic interaction. The experience and recommendations of combinational antifungal therapy for cryptococcal infections, systemic candidiasis, invasive aspergillosis and other rare mold infections have been presented in this review, giving some information on mechanism of action and principles in combined use of mycotic anti-infectives. Most experience of combination therapy approaches are in adult patients; but in fact, there is no conclusive data documenting definite benefits of this approach, either in adults or children.